Analysis of the effect of the fluid-structure interface on elastic wave velocity in cornea-like structures by OCE and FEM. (17th February 2016) - Han, Zhaolong; Li, Jiasong; Singh, Manmohan; Vantipalli, Srilatha; Aglyamov, Salavat R; Wu, Chen; Liu, Chih-hao; Raghunathan, Raksha; Twa, Michael D; Larin, Kirill V
Abstract: Air-pulse optical coherence elastography (OCE) is a promising technique for quantifying biomechanical properties of the cornea. This technique typically involves imaging and analysis of the propagation of the air-pulse induced elastic waves to reconstruct corneal biomechanical properties using an analytical model. However, the effect of the fluid-structure interface (FSI) at the corneal posterior surface on the elastic wave velocity is not accounted for in many models. In this study, we examined the effect of the FSI with OCE experiments on contact lenses with and without fluid in the posterior gap. Finite element models (FEM), also with and without the FSI, were constructed to simulate the elastic wave propagation based on the OCE measurements. The FEM and OCE results were in good agreement demonstrating the feasibility of the method. To further investigate the effect of the FSI, OCE experiments and subsequent FEM simulations were conducted on in situ rabbit corneas before and after rose bengal/green light corneal collagen cross-linking (RGX). Both the OCE experiments and the FE simulations demonstrated that the FSI significantly reduced the group velocity of the elastic wave, and thus, should be considered when determining corneal biomechanical properties from an appropriate mechanical model. By matching the FEM-calculated velocity to the OCE-measured velocity, the corneal elasticity was quantified. The Young's modulus of the rabbit cornea before RGX was E = 65 ± 10 kPa at a controlled intraocular pressure (IOP) of 15 mmHg. After RGX, the Young's modulus increased to E = 102 ± 7 kPa at the same IOP.